2019
DOI: 10.1186/s12882-019-1437-4
|View full text |Cite
|
Sign up to set email alerts
|

Saliva for assessing creatinine, uric acid, and potassium in nephropathic patients

Abstract: Background Lab tests on saliva could be useful because of low invasivity. Previous reports indicated that creatinine, uric acid, and potassium are measurable in saliva. For these analytes the study investigated methodology of saliva tests and correlations between plasma and saliva levels. Methods The study enrolled 15 healthy volunteers for methodological analyses and 42 nephropathic patients for plasma-saliva correlations (35 non-dialysis and 7 dialysis). Saliva was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
(29 reference statements)
3
26
0
Order By: Relevance
“…Concentrations of UA in the saliva of healthy individuals is 199 ± 27 μmol/L and comparable to concentrations 120-400 μmol/L observed in the serum [6]. Earlier studies reported a linear relationship between serum and salivary UA levels in most cases [1,6,[9][10][11][12].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Concentrations of UA in the saliva of healthy individuals is 199 ± 27 μmol/L and comparable to concentrations 120-400 μmol/L observed in the serum [6]. Earlier studies reported a linear relationship between serum and salivary UA levels in most cases [1,6,[9][10][11][12].…”
Section: Introductionsupporting
confidence: 69%
“…Unfortunately, these tests were performed only with a single participant. Bilancio et al [12] compared effect of storage, time of collection, day-to-day variability, and site of collection of UA in saliva. Mid-morning saliva had lower levels of 184 ± 102 μmol/L while standard morning saliva content was 261 ± 166 μmol/L.…”
Section: Saliva Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a reactive oxygen species scavenger, it helps stabilize arterial pressure and oxidative stress [21,[34][35][36]. In turn, alterations in its levels in saliva were associated with acute stress [34] and different local and systemic pathologies such as oral lichen planus [37] or nephropathies [38]. Previous studies that evaluated salivary uric acid in patients with BMS did not find statistically significant changes as compared with healthy controls [16,20], although these studies did not make corrections for total protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, salivary constituents of serum origin can reflect the abnormalities in the blood composition associated with systemic diseases [ 9 , 10 ]. In patients with chronic kidney disease (CKD), higher contents of urea, uric acid and creatinine in saliva were found [ 11 13 ]. Salivary levels of cortisol, nitrite, uric acid, sodium, chloride, pH, amylase, and lactoferrin have been reported to be markers related to end-stage renal disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%